Genre analysis and tourism promotional texts: a literature review - Alali, Bashar Abdulkareem; Mohamad Ali, Afiza; Sahar, Rafidah; Md Zamin, Ainul Azmin (Kulliyyah of Languages & Management, IIUM Pagoh, 2021)
Recent years have seen significant growth in genre analysis in English for Specific Purposes (ESP), specifically in academic and professional contexts. This paper reviews the use of genre analysis method and its models in analysing tourism promotional genres. Related studies were searched in online databases and google scholar using the keywords: genre analysis, genre-based analysis, tourism, and ESP. This paper found that very few studies conducted on tourism promotional genres used genre analysis and discovered that Swales (1990), Bhatia (1993, 2004) and Kathpalia (1992) were the most used models in analysing tourism promotional genres. It concluded with recommendations for further genre analysis studies in the tourism field